Pelatihan Pencatatan Pembukuan Sederhana Pada Industri Rumahan Di Desa Kalangan Bantul - Vidya Dina Indaryanti; Ika Wulandari (Institut Nalanda, 2023)
Bookkeeping records are very important for the running of a business. Based on bookkeeping records to become a financial report that will provide information about the amount of profit and loss obtained. Home industry entrepreneurs in Kalangan Village, Baturetno, Banguntapan, Bantul do not understand bookkeeping records and the separation of personal and business finances. These problems are known based on interviews with business owners. Based on these problems, this community service activity was carried out with the aim of providing information about bookkeeping records for home industry businesses through training in simple bookkeeping records. The methods used in this community service activity are 1) Survey 2) Training and Socialization 3) Evaluation. This community service activity has the result that business owners begin to understand the importance of financial reports so that business owners begin to record simple bookkeeping and can separate personal financial records from business finances.